Chronic hypoxia impairs skeletal muscle repair via HIF‐2α stabilization - Amelia Yin; Wenyan Fu; Anthony Elengickal; Joonhee Kim; Yang Liu; Anne Bigot; Kamal Mamchaoui; Jarrod A. Call; Hang Yin (Wiley, 2024)
Abstract Background Chronic hypoxia and skeletal muscle atrophy commonly coexist in patients with COPD and CHF, yet the underlying physio‐pathological mechanisms remain elusive. Muscle regeneration, driven by muscle stem cells (MuSCs), holds therapeutic potential for mitigating muscle atrophy. This study endeavours to investigate the influence of chronic hypoxia on muscle regeneration, unravel key molecular mechanisms, and explore potential therapeutic interventions. Methods Experimental mice were exposed to prolonged normobaric hypoxic air (15% pO2, 1 atm, 2 weeks) to establish a chronic hypoxia model. The impact of chronic hypoxia on body composition, muscle mass, muscle strength, and the expression levels of hypoxia‐inducible factors HIF‐1α and HIF‐2α in MuSC was examined. The influence of chronic hypoxia on muscle regeneration, MuSC proliferation, and the recovery of muscle mass and strength following cardiotoxin‐induced injury were assessed. The muscle regeneration capacities under chronic hypoxia were compared between wildtype mice, MuSC‐specific HIF‐2α knockout mice, and mice treated with HIF‐2α inhibitor PT2385, and angiotensin converting enzyme (ACE) inhibitor lisinopril. Transcriptomic analysis was performed to identify hypoxia‐ and HIF‐2α‐dependent molecular mechanisms. Statistical significance was determined using analysis of variance (ANOVA) and Mann-Whitney U tests. Results Chronic hypoxia led to limb muscle atrophy (EDL: 17.7%, P < 0.001; Soleus: 11.5% reduction in weight, P < 0.001) and weakness (10.0% reduction in peak‐isometric torque, P < 0.001), along with impaired muscle regeneration characterized by diminished myofibre cross‐sectional areas, increased fibrosis (P < 0.001), and incomplete strength recovery (92.3% of pre‐injury levels, P < 0.05). HIF‐2α stabilization in MuSC under chronic hypoxia hindered MuSC proliferation (26.1% reduction of MuSC at 10 dpi, P < 0.01). HIF‐2α ablation in MuSC mitigated the adverse effects of chronic hypoxia on muscle regeneration and MuSC proliferation (30.9% increase in MuSC numbers at 10 dpi, P < 0.01), while HIF‐1α ablation did not have the same effect. HIF‐2α stabilization under chronic hypoxia led to elevated local ACE, a novel direct target of HIF‐2α. Notably, pharmacological interventions with PT2385 or lisinopril enhanced muscle regeneration under chronic hypoxia (PT2385: 81.3% increase, P < 0.001; lisinopril: 34.6% increase in MuSC numbers at 10 dpi, P < 0.05), suggesting their therapeutic potential for alleviating chronic hypoxia‐associated muscle atrophy. Conclusions Chronic hypoxia detrimentally affects skeletal muscle regeneration by stabilizing HIF‐2α in MuSC and thereby diminishing MuSC proliferation. HIF‐2α increases local ACE levels in skeletal muscle, contributing to hypoxia‐induced regenerative deficits. Administration of HIF‐2α or ACE inhibitors may prove beneficial to ameliorate chronic hypoxia‐associated muscle atrophy and weakness by improving muscle regeneration under chronic hypoxia.